DFT insights into the electronic properties and adsorption mechanism of HS− on smithsonite (1 0 1) surface. (September 2019) - Zhao, Wenjuan; Liu, Dianwen; Feng, Qicheng; Wen, Shuming; Chang, Weihua
Graphical abstract: Highlights: HS − ions can stably adsorb onto smithsonite (1 0 1) surface. A newly stable ZnS structure forms on smithsonite surface. HS − ions spontaneously react with Zn atoms at top, bottom, and bridge sites. Slight oxidation occurs during the sulfidization of smithsonite. Abstract: Sulfidization flotation is commonly used to recover zinc oxide minerals from ores, and sulfidization is a critical stage. However, few studies on the microscopic mechanism of smithsonite sulfidization have been performed. In this work, density functional theory calculations are conducted to investigate the electronic properties and adsorption mechanism of sulfide ion species on smithsonite (1 0 1) surface. Results indicate that the ZnO bond breaks when smithsonite crystal is crushed and ground, and that zinc atoms are the dominant reactive sites for the subsequent adsorption of flotation reagents onto smithsonite surface. HS − ions can spontaneously react with Zn atoms at the top, bottom, and bridge sites of the mineral-surface layer, thereby forming a newly stable structure of ZnS on smithsonite (1 0 1) surface. The adsorption of HS − ion on this smithsonite surface greatly influences the structural and electronic properties of smithsonite (1 0 1) surface, changing the structure of ZnO and CO at the surface layer of smithsonite. We observe an obvious electron transfer between Zn and S atoms after HS − ion adsorption, as well as a significant difference in charge transfer when HS − ion adsorbs at different Zn sites on mineral surface. Besides, it proves that a slight oxidation occurs in the sulfidization process of smithsonite at the atomic level.